Relación entre estados de ánimo y rendimiento en voleibol masculino de alto nivel - Ricardo de la Vega Marcos (Revista de Psicología del Deporte, 2014)
The present study , using a retrospective ex post facto design , analyzed the relationship between precompetitive mood states andthe sports performance of a team of twelve volleyball players during the World Championship Brazil 2011 , men's sub - 20.For measuring instrument moods Profile of moods states ( POMS ) was used . The measurement of athletic performance was held from two instruments : first , a rating scale or coaches perceived performance of their purpose jugadoresy other, the volleyball Data System software. We proceeded with descriptive statistics and non-parametric inferential statistics. Participants mostraronun high profile psychic force , moderate tension , low anger, and high fatigue and depression. The relationship between these variables and the fact sediscute how to lose a game that resulted in the disqualification of the team the chance to win a medal, influenced to a menortensión and force players is detailed , as well as increased depression and fatigue.